The Influence Pubbesannivasa in Theravada Buddhist Texts - Akkhachat, Manit; Chaimalee, Wutikrai; Anonjarn, Banyat (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
This documentary study aimed (1) to study the meaning of Pubbesannivāsa, (2) to study the causes of Pubbesannivāsa, and (3) to study the influence of Pubbesannivāsa in Theravada Buddhist texts. It was found that Pubbesannivāsa referred to the co-living in the previous life. The causes of Pubbesannivāsa in Theravada Buddhist texts were classified into three aspects as follows: 1) good deeds, 2) bad deeds, and 3) Neutral deeds. The influence of Pubbesannivāsa in Theravada Buddhist texts was found in the four values as follows: 1) the literature model of Suttanipata Atthakatha, 2) the literature model of Dhammapada Atthakatha, 3) the literature model of Samantapasadika Atthakatha, and 4) the literature of Sammohavinothani Atthakatha.